Avian influenza: the looming threat of Disease X and lessons from Poland and Europe - Andrzej Jarynowski; Andrzej Jarynowski; Stanisław Maksymowicz; Maja Romanowska; Ireneusz Skawina; Ireneusz Skawina (European Journal of Translational and Clinical Medicine)
The ongoing outbreak of highly pathogenic avian influenza such as A/H5N1 virus, with its continued evolution and spread to various mammalian species, raises significant concerns about its potential to cause a human pandemic. This editorial examines the recent spillover events to mammals, the economic impact on the poultry industry and the importance of preparedness and preventive measures. The situation in the USA (widespread outbreaks in cows as well as in dairy farm workers) and in Europe (infections in cats and fur animals) highlights the urgency of implementing effective surveillance, biosecurity, vaccination and communication strategies. Particularly, we focus on the lessons learnt (and also those not learnt) from Poland and the rest of Europe in managing potentially being zoonotic outbreaks of unknown origin. Personal experience from these events, though potentially reflecting the subjective views of the authors, highlight the importance of regional preparedness and rapid response to mitigate the risks posed by avian influenza and other emerging infectious diseases. A One Health approach, integrating the animal, human and environmental health sectors with socioeconomic constraints, is crucial for mitigating the risks and preventing a potential global health crisis.